Estudo dos nomes do patrimônio cultural material de Palmas - TO: - Bastiani, Carla (2023)
The general objective of this thesis is to understand toponomastic studies in the scope of Basic Education, specifically aimed at Elementary School, in the context of what the multiliteracies approach proposes. Aiming of integrating Toponomastics in the range of contents covered in the classroom, didactic proposals were elaborated for the development of such work, in accordance with the essential learning that have been established by the official documents that guide Basic Education, both nationally, such as the BNCC (2017), and regionally, with emphasis on DCT - Elementary Education (2019). These didactic proposals involve the reading and production of discursive genres, which, besides contributing to the development of the student's competence as a language user, from the guiding axis of the toponym, can lead him to perceive how it is integrated to the history of the place, leading him to understand the importance of cultural roots for the constitution of his own identity. The thematic basis for the development of such proposals were the names of the material heritage assets of the city of Palmas - TO. The justification for the choice of this toponymic set was the urgent need to carry out actions aimed at raising awareness about the importance of valuing the history of the community, fostering, above all, heritage education. In this sense, we defend the thesis that heritage assets represent for the community much more than undifferentiated spaces and should be understood as real places according to the prism of Humanistic Geography. Considering the context of the digital society and the desire to work with place names in elementary school in a meaningful way, the idea of developing a digital didactic resource based on the names of the city's heritage places was conceived. From this aspiration, the topomastic software "On the Heritage Trail" was born, whose idea is to serve as another expedient for the insertion of Toponomy in the school environment, making the student's experience with the approach of toponyms more interactive by mobilizing a digital tool in favor of the construction of learning. As for the methodology, this research is characterized as qualitative, and the inductive method was used for the construction of the hypotheses in the onomastic descriptions. The research corpus was collected from official sources in the municipality and consists of seven names of heritage properties. The motivations for these toponyms were sought in documental and bibliographic sources and systematized in sheets. The sheet presented was adapted from the models elaborated by Dick (2004), Faria (2017) and Ferreira (2019). The results point to the fact that it is possible to develop actions that contemplate the work with the toponym in the context of Basic Education in agreement with what is laid out in the normative educational documents. Regarding the names of heritage assets, this work can contribute to the awakening of awareness of appreciation and preservation of these places, to the extent that students can recognize them as a framework of their cultural heritage, the essence of what is characterized as heritage education.